Electronic excitation induced modifications in the ferroelectric polarization of BiFeO3 thin films - Ravalia, Ashish; Kataria, Bharat; Katba, Savan; Jethva, Sadaf; Vagadia, Megha; Asokan, K.; Gautam, Sanjeev; Chae, Keun Hwa; Kuberkar, D. G. (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
We report the effect of electronic excitations induced modifications in the ferroelectric polarization in BiFeO3 (BFO) multiferroic films grown on 0.2% Nb doped SrTiO3 (SNTO) substrates by pulsed laser deposition. The BFO/SNTO films were irradiated with 200 MeV Ag+15 ions with ion fluences of 5 x 10(10) to 5 x 10(12) ions/cm(2) and characterized by using X ray diffraction (XRD), atomic force microscopy (AFM), ferroelectric polarization and near-edge X-ray absorption fine structure (NEXAFS) measurements. The XRD and AFM results show the creation of structural defects and oxygen vacancies by ion irradiation. Such defects induced enhancement in structural strain and reduction in mobility of charge carriers leading to the improvement in ferroelectric behaviour in BFO films. In addition, the local electronic structures investigated using NEXAFS studies reveal the significant change in spectral features suggesting the role of Bi-O and Fe-O hybridizations that modifies the ferroelectric behaviour of BFO films. These results are used to understand the mechanism.
Keywords: DOPED BIFEO3; HEAVY-IONS; THICKNESS; MN